1993
DOI: 10.1111/j.1749-7345.1993.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fish Larvae Feeding: Formulated Diets or Live Prey?

Abstract: In the rearing of larval marine fish, any diet that reduces dependance on live prey production is of technical and economic interest. Weaning juveniles with a completely developed digestive tract to a conventional diet, (i.e., “late weaning”) can be successful in any marine fish species. For example, weaning one‐month‐old sea bass (20 mg) to the study's reference diet, Sevbar, resulted in over 85% survival (40% from hatching) and 1.25 g fish at day 90 (at 19 C) In contrast, “early weaning” of larvae to special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
1
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(131 citation statements)
references
References 23 publications
8
111
1
8
Order By: Relevance
“…Carrageenan containing pellets are suitable for the ayu, Plecoglossus altivellis (Teshima et al, 1982), but not for postlarval tongue sole (Cynoglossus semilaevis) (Liu et al, 2008). Both alginate and zein appear to be suitable for farming larvae of sea bass (Dicentrarchus labrax) (Person Le Ruyet et al, 1993) but not barramundi (Lates calcalifer) (Partridge & Southgate, 1999), although Lee et al (1996) previously reported that Lates calcifer larvae were able to digest both alginate and gelatine bound diets. Sodiumcarboxymethilcellulose, sodium alginate and gelatin included in feed for postlarval tongue sole (Cynoglossus semilaevis) brought about a growth similar to controls (Liu et al, 2008).…”
Section: Fishmentioning
confidence: 99%
“…Carrageenan containing pellets are suitable for the ayu, Plecoglossus altivellis (Teshima et al, 1982), but not for postlarval tongue sole (Cynoglossus semilaevis) (Liu et al, 2008). Both alginate and zein appear to be suitable for farming larvae of sea bass (Dicentrarchus labrax) (Person Le Ruyet et al, 1993) but not barramundi (Lates calcalifer) (Partridge & Southgate, 1999), although Lee et al (1996) previously reported that Lates calcifer larvae were able to digest both alginate and gelatine bound diets. Sodiumcarboxymethilcellulose, sodium alginate and gelatin included in feed for postlarval tongue sole (Cynoglossus semilaevis) brought about a growth similar to controls (Liu et al, 2008).…”
Section: Fishmentioning
confidence: 99%
“…This is a major bottleneck for larval culture, due primarily to their small size and often poorly developed digestive system (Person Le Ruyet, et al, 1993). Many marine fish larvae require motile prey organisms (Pedersen et al, 1987;Pedersen and Hjelmeland, 1988).…”
Section: First Feedingmentioning
confidence: 99%
“…The SS type rotifer (Super small rotifers) ranges between 100-120 µm, which are preferred for the first feeding of fish larvae with small mouth openings (rabbitfish, groupers, and other fish with mouth openings less than 100 µm at first feeding). Those rotifers, however, are not genetically isolated from Sstrains, but are smaller than common S-strains (Person Le Ruyet, et al, 1993). The last strain was an SS rotifers from the University of Ghent, Belgium, that were genetically modified to resist warmer temperatures (above 30 ºC).…”
Section: Rotifersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially, relevant in sea bass larval rearing, where live food accounts for 79% of the production cost for juveniles up to 45 days old. In the first 3 months of life, live food represents 50% of the feed cost even though they constitute only 1.6% of the total dry weight of food required (Person-Le Ruyet et al, 1993). Nowadays, more studies are focused on early weaning and its effects on digestive physiology related to studies on the development of the digestive system and gastrointestinal physiology of marine fish larvae.…”
Section: Introductionmentioning
confidence: 99%